PENGARUH PENERIMAAN PAJAK BUMI DAN BANGUNAN TERHADAP OPTIMALISASI PENCAPAIAN TARGET PENDAPATAN ASLI DAERAH KOTA BANDUNG TAHUN 2017-2021 - Nurajijah; Rubiar Rachman, Fatwa; Dzulfiqar , Imam (Jurnal Nusa Akuntansi, 2024)
This research aims to find out how much influence the Rural and Urban Land and Building Tax (PBB-P2) has on regional original income (PAD) in the City of Bandung. Based on target data and the realization of the effectiveness and contribution of regional taxes to Bandung City's original regional income, there is a decrease in the realization of achievements from year to year. This is influenced by less than optimal land and building tax collection in the urban and rural sectors. The data processing is based on the realization of land and building tax targets as well as regional original income data with an observation period from 2017 to 2021 and secondary data in the form of monthly data for 5 years. The results show that the average contribution of land and building tax to local revenue only produces a ratio of 16%. From the results of hypothesis testing, there is a significant influence between PBB-P2 and the Bandung City PAD